Secure D2D underlaying cellular communication based on artificial noise assisted - Xiao-lei KANG; Xin-sheng JI; Kai-zhi HUANG (Tongxin xuebao)
A secure communication scheme based on artificial noise assisted from base station(BS)was proposed to improve the system secrecy rate of the D2D underlaying cellular.Firstly,the system secrecy rate was modeled.Then the BS with multi-antennas added artificial noise(AN)in cellular user’s signal as well as designed beam vectors of the desired signal and artificial noise to maximize system secrecy rate.In the end,a joint optimization scheme based on the fairness constraint was introduced to optimize beam vectors of the desired signal,the power allocation for BS’s information signal and AN and the D2D power control.Simulation results show that the system ergodic secrecy rate can be improved 2.7 bit·s−1·Hz−1more than the schemes based on SVD and zero-forcing at most.